2021
DOI: 10.1016/j.jbc.2021.100726
|View full text |Cite
|
Sign up to set email alerts
|

PIP2 regulation of TRPC5 channel activation and desensitization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
(82 reference statements)
2
30
0
Order By: Relevance
“…Based on the findings described above, we wondered whether AC1903—which is typically used as a TRPC5 inhibitor at concentrations of 30–100 μM in cellular assays ( 29 , 56 )—might have limited selectivity for TRPC5 channels and whether its effect on intracellular G418 levels and PTC readthrough might be the consequence of inhibition of other or multiple targets. All well-characterized TRPC channel inhibitors reported to date modulate multiple TRP(C) channels ( 34 , 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings described above, we wondered whether AC1903—which is typically used as a TRPC5 inhibitor at concentrations of 30–100 μM in cellular assays ( 29 , 56 )—might have limited selectivity for TRPC5 channels and whether its effect on intracellular G418 levels and PTC readthrough might be the consequence of inhibition of other or multiple targets. All well-characterized TRPC channel inhibitors reported to date modulate multiple TRP(C) channels ( 34 , 35 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…As part of the development of AC1903, the compound was screened against a standard kinase panel, in which no off-target effects were found ( 29 ). In cellular experiments, AC1903 is typically used as a TRPC5 inhibitor at concentrations of 30 to 100 μM ( 29 , 56 ). However, our data suggest that TRPC3, TRPC4, TRPC6, and TRPV4 channels are important potential off-targets of AC1903 at these concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…PIP 2 , phosphatidylinositol (4,5) bisphosphate.
Figure 3 PKC can regulate the activity of ion channels in a PIP 2 -dependent manner ( 31 , 39 , 57 , 58 , 63 , 95 , 173 ). Examples of ion channels where PKC regulation of their activity has been linked to alteration of channel–PIP 2 interactions.
…”
Section: Phosphorylation Of Ion Channels By Pkcmentioning
confidence: 99%
“…This residue is part of a VT 972 TRL motif, and it is likely that PKC phosphorylation at T972 may control the interaction of TRPC5 with PDZ domains of other proteins, such as Na + /H + exchanger regulatory factor (NHERF), precluding channel interactions with DAG ( 37 , 38 ). Using an elegant optogenetic tool to control rapid dephosphorylation of PIP 2 , it was recently shown that PKC-induced desensitization of TRPC5 through Thr972 is caused by weakening channel–PIP 2 interactions ( 39 ). In contrast, DAG enhanced channel–PIP 2 interactions and activated the channel ( 39 ).…”
Section: Transient Receptor Potential Channelsmentioning
confidence: 99%
See 1 more Smart Citation